The Effect of Measuring Ambulatory Blood Pressure on Nighttime Sleep and Daytime Activity—Implications for Dipping - Agarwal, Rajiv (American Society of Nephrology, 2010)
Background and objectives: Ambulatory blood pressure (BP) monitoring is commonly used to assess the circadian pattern of BP. Circadian BP pattern is influenced by physical activity and sleep cycle. The effect of BP monitoring itself on the level of physical activity and sleep remains unknown. If BP monitoring affects these parameters, then monitoring itself may influence the circadian BP pattern. Design, setting, participants, & measurements: To assess the effect of ambulatory BP monitoring on sleep duration, sleep efficiency, and daytime activity, we measured physical activity using wrist actigraphy in 103 veterans with chronic kidney disease. After 6 to 7 days of continuous activity monitoring, participants underwent ambulatory BP monitoring with simultaneous actigraphy. The above experiment was repeated after 1 mo. Results: Among the top tertile of patients (most sleep), when wearing ambulatory BP patients spent less time in bed at night (−92 min, P < 0.0001), were less asleep during those hours (−98 min, P < 0.0001), and had reduced sleep efficiency (82% versus 77%, −5% P = 0.02). On the day of ambulatory BP monitoring, patients were more sedentary during waking hours (+27 minutes, P = 0.002). During ambulatory BP monitoring, waking after sleep onset more than median was associated with greater odds for nondipping (odds ratio 10.5, P = 0.008). Conclusions: Ambulatory BP monitoring is associated with disturbed sleep and reduced physical activity, characteristics that influence dipping. Ambulatory BP monitoring may itself induce nondipping and may thus mitigate the prognostic significance of the dipping phenomenon.